Modeling Online Loan Risk Dynamics with SEIQRL, Regulation, and Financial Literacy Analysis in Indonesia - Christari Lois Palit; Agresia Servina Sabubun; Dyrel Samuel Kusnadi; Julius Zendrato; Mikha Rajagukguk; Tessy Angraini Mokodanga (Griya Journal of Mathematics Education and Application, 2026)
This study examines the dynamics of risky online lending behavior in Indonesia using the SEIQRL mathematical model. The model extends the SEIR approach by adding Quarantined (Q) and Literate (L) compartments to represent regulatory intervention and financial literacy. This study aims to construct the SEIQRL model, analyze the risk-free equilibrium point, calculate the basic reproduction number (R₀), and evaluate the effects of regulation and financial literacy on the spread of risky online lending behavior. The method uses a quantitative approach based on mathematical modeling and numerical simulation with Wolfram Mathematica. The results show that the baseline scenario produces an R₀ value of 6.1538, indicating that risky online lending behavior can spread strongly within the population. Strong regulation and strong literacy scenarios reduce the risk, but they do not fully control its spread. The combined regulation and literacy scenario produces an R₀ value of 0.8696, meaning the risk can be controlled because R₀ < 1. These findings show that controlling risky online lending cannot rely only on access restrictions or service blocking. Early financial literacy must also serve as a preventive strategy. The SEIQRL model can support policy analysis for controlling online lending risks in Indonesia.